Literary Magic in The BFG: Crafting a Timeless Tale of Children Literature - Nuzulia, Rahma (Saree: Research in Gender Studies, 2024)
ABSTRACT ENGLISHThe purpose of this study is to investigate the literary strategies that Roald Dahl utilized in his novel "The BFG" in order to create a piece of children's literature. The study focuses on the novel's innovative use of language, character development, and thematic elements in order to gain an understanding of how these elements contribute to the novel's enduring appeal. The existing data for analysis is derived directly from a tangible interaction with the text, which ensures that the analysis is accurate to the material that was initially being analyzed. When it comes to expanding the scope of analysis, scholarly articles, critical books, and findings from previous research, are also very significant. Furthermore, the research investigates the influence that "The Big Friendly Giant" has had on children's literature, focusing on the educational contributions it has made and the impact it has had on subsequent works. The purpose of this study is to produce a comprehensive understanding of Roald Dahl's narrative strategies and the significance of those strategies within the context of children's literature. This will be accomplished through a qualitative analysis of primary and secondary sources. ABSTRACT INDONESIANTujuan dari penelitian ini adalah untuk menyelidiki strategi sastra yang digunakan Roald Dahl dalam novelnya “The BFG” untuk menciptakan sebuah karya sastra anak. Penelitian ini berfokus pada penggunaan bahasa, pengembangan karakter, dan elemen tematik yang inovatif dalam novel tersebut untuk mendapatkan pemahaman tentang bagaimana elemen-elemen tersebut berkontribusi pada daya tarik novel yang bertahan lama. Data yang ada untuk analisis diperoleh langsung dari interaksi nyata dengan teks, yang memastikan bahwa analisis tersebut akurat terhadap materi yang pada awalnya dianalisis. Dalam hal memperluas cakupan analisis, artikel-artikel ilmiah, buku-buku kritis, dan temuan-temuan dari penelitian sebelumnya, juga sangat signifikan. Selain itu, penelitian ini juga menyelidiki pengaruh “The Big Friendly Giant” terhadap literatur anak-anak, dengan fokus pada kontribusi pendidikan yang diberikan dan dampaknya terhadap karya-karya berikutnya. Tujuan dari penelitian ini adalah untuk menghasilkan pemahaman yang komprehensif mengenai strategi naratif Roald Dahl dan pentingnya strategi tersebut dalam konteks literatur anak-anak. Hal ini akan dicapai melalui analisis kualitatif dari sumber-sumber primer dan sekunder.